Representasi Kebudayaan Arab yang terdapat dalam Novel "Al Hafeedatu Al Ameerikiyah" Karya Inaam Kajah Jii (Kajian Antropologi Sastra) - Wiwil Nofrizul Saputri; Muhammad Ilham (El-Syaker : Samarinda International Journal of Language Studies, 2025)
Representation of Arab culture is a depiction of all forms of cultural reality that occur in the Arab region. These depictions can include social aspects, multicultural interactions and natural phenomena. In the current era, the development of Arabic culture began to be eroded by the development of the Western world. One of the efforts to promote Arabic culture again is by modernizing it in accordance with Islamic corridors that do not eliminate the essence of its values and culture. So that Muslims can easily accept the renewal. This research uses descriptive qualitative research. The data sources used are primary data and secondary data. The techniques used are reading techniques and note-taking techniques. The data analysis stage is divided into three parts, namely the data condensation stage, data representation and data inference. The representation of Arabic culture contained in this novel can be described through the elements of literary anthropology. The elements of literary anthropology contained in this novel are social culture, material culture and ecological culture. The results of the data obtained from social culture found 4 data findings. Material culture found 20 data and ecological culture found 7 data findings. With these various elements, the Arabic culture found in Iraq is increasingly recognized by some Americans who are doing state duties in Iraq. In general, the results of this study are expected to be useful for the development of literary science, especially in the field of literary anthropology.